Methodical Aspects of Realization of a Lesson with the Help of the Pedagogical Software “Algebra, 7 Classes” - Shishko, Л.С. (Journal of Information Technologies in Education (ITE), 2008)
In this article is described the purpose of the pedagogical software “Algebra, 7 classes” and its basic descriptions, and also methodical aspects of realization of a lesson in network variant.